Indonesia's Directive Legislation: Balancing with Pancasila Law-Idea - Hermanto, Bagus; Subawa, Made; Hattori, Mariko; Ivory, Jared (Pancasila: Jurnal Keindonesiaan, 2024)
The implementation of the Omnibus Law in the formation of laws and regulations in Indonesia commenced with the introduction of directive legislation in a range of sectors. Conversely, the Omnibus Law has given rise to a number of issues, particularly in relation to the Pancasila law-idea. This is because the Omnibus Law is perceived to be at odds with the Pancasila law-idea, with critics arguing that it fails to reflect the spirit of Pancasila in terms of both practice and legislative methodology. This paper aims to examine, evaluate and identify potential avenues for the development of national regulations in alignment with the principles of the Omnibus Law, taking into account the role of Pancasila as an ideological and legal foundation. This paper demonstrates that the Pancasila idea-law can serve to balance and harmonise the various understandings held by countries around the world, particularly in relation to the application of the Pancasila law-idea as a foundation in the practice of Omnibus Law and the formation of national regulations.